An analysis of the level of client self-disclosure in code-switches during individual counseling - Carlile, Christopher John (Animo Repository, 1992)
This is a descriptive study dealing with the problem of client code-switching during individual counseling. Subjects for the study were clients of counselors from one university. Counselors included 5 males and 3 females. Clients were 6 females and 8 males. A total of 15 interview typescripts were collected for analysis including a profile sheet indicating counselor and client language preference. All client code-switches were identified and placed on individual 4 x 6 index cards. These were then judged by 3 graduate level counseling students. Each code-switch was judged according to low or high levels of self-disclosure in the topic content. Cards not unanimously classified after 2 judgings were placed aside. The results showed a higher frequency of client switches into the preferred language (57.33). In the high disclosing category 55.42 were switches into the preferred language. For statistical treatment a Chi-square analysis was used with a Phi-coefficient. Considering all the classified client code-switches no significant relationship was found between levels of disclosure and code-switching. However, when the data was broken down into intra-sentence (by the one speaker) and inter-sentence (between speakers) categories a different picture emerged. Whilst the intra-sentence switching was not significant the inter-sentence code-switching was significant: X2 (1, N = 107) = 5.7090 (p .02) with a Phi-coefficient of o The conclusions reached are as follows:1) Code-switching is a regular occurrence in counseling in the Philippines.2) There is a greater frequency of clients code-switching into their preferred language for both low and high self-disclosures.3) Clients who code-switch to their non-preferred language in responding to a counselor intervention in the client's preferred language will probably not make a high-disclosure. The researcher makes two recommendations. First, the replication of this study with a larger sample group and greater control of variables. Second, that research be undertaken into inter-sentence code-switching by clients during individual counseling.